Use of sexed bulletin sperm as a biotechnological tool for intensifying dairy cattle reproduction - Pryshedko, Vladimir M.; Pryshedko, V. M.; Pryshedko, V.; Prishedko, V.; Pryshed’ko, Vladimir; Pryshedko, Volodymyr; Pryshedko, Volodymyr Mykhailovych; Пришедько, Володимир Михайлович; Halaktenov, Dmytro Oleksandrovych; Галактенов, Дмитро Олександрович; Zaitseva, Oleksandra Romanivna; Зайцева, Олександра Романівна; et al. (Sergeieva&Co, Karlsruhe, Ukraine & Germany, 2025)
The article investigates the effectiveness of using sexed semen to improve reproductive performance in a Holstein dairy herd at an industrial farm in northern Ukraine. It was found that the average milk yield per cow over 305 lactation days was 9,435 kg, with a milk fat content of 3.86%. The best reproductive results were observed in cows with medium productivity levels. A decline in reproductive parameters was noted when milk yields exceeded 6,500–7,500 kg per year. The use of sexed semen led to an increase in the number of female calves born. Initially, it was used only for heifer insemination, but over time, it was also applied to cows after first calving. Pregnancy rates with sexed semen were 42–43% in heifers and 35–36% in first-calf cows. In comparison, conventional semen showed higher pregnancy rates — 61–65% in heifers and 42–50% in first-calf cows. The proportion of female calves from sexed semen was 88%, compared to only 51% with conventional semen. The use of sexed semen contributes to herd rejuvenation, reduces the shortage of replacement heifers, and enhances the efficiency of genetic selection. Досліджено ефективність використання сексованої сперми для покращення відтворення стада голштинської молочної худоби на промисловій фермі на півночі Україні. Було встановлено, що середній удій молока на корову за 305 днів лактації становив 9 435 кг, а вміст жиру в молоці — 3,86 %. Найкращі відтворні якості спостерігалися у корів із середнім рівнем продуктивності. Зниження репродуктивних показників відзначалося у тварин з надоєм понад 6 500–7 500 кг. Використання сексованої сперми дозволило збільшити кількість народжених самок. Спочатку сперму розділену за статтю застосовували лише для осіменіння телиць, але згодом почали використовувати й для корів після першого отелення. Рівень запліднення сексованою спермою становив 42–43 % у телиць і 35–36 % у корів. Для порівняння, при використанні звичайної сперми рівень запліднення був вищим — 61–65 % у телиць і 42–50 % у корів. Частка самок серед телят від сексованої сперми становила 88 %, тоді як від звичайної — лише 51 %. Застосування сексованої сперми сприяє омолодженню стада, вирішує проблему отримання ремонтних телиць і підвищує ефективність генетичного відбору.
Використання сексованої сперми бугаїв як біотехнологічного інструменту інтенсифікації відтворення молочної худоби
Пришедько Володимир Михайлович https://orcid.org/0000-0002-7324-5458
Keywords: sexed semen; сексована сперма; dairy cattle; молочна худоба; productive traits; продуктивність; reproductive performance; відтворна здатність